The Making of Conservation Science: Report on the Brill-Nuncius Seminar on the Material and Visual History of Science, organized by Sven Dupré (Utrecht University/University of Amsterdam) and Esther van Duijn (Rijksmuseum Amsterdam), 29–30 April 2021. Issue 1 (1st July 2021) - Žakula, Tijana
Abstract : On 9 October 1947, the National Gallery in London opened the Exhibition of Cleaned Pictures. Some seventy masterpieces that had undergone various treatments since 1936 were brought together and exhibited in this groundbreaking show. Much criticized, but also praised by many, the exhibition sparked the so-called "cleaning controversy." It goes without saying that both the exhibition as well as the ensuing controversy impacted generations of scholars of all stripes. So much so that the exhibition was mentioned in virtually all the lectures that were delivered during the Brill Nuncius seminar held on 29–30 April 2021, which focused on the formation of conservation science in the post-World War II period, from the 1940s through the 1970s.